Effectiveness of Ethanol Extract Clove Leaves (Syzygium aromaticum) In Inhibiting Biofilm of Candida Albicans ATCC 14053 - Nuzula, Firdausi; Masfufatun, Masfufatun (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Candida albicans is the most common type of Candida. It is a normal microbiota in the healthy human body that can become pathogenic when its balance is disturbed, causing an infection referred to as candidiasis. Antifungal resistance to biofilms is estimated to be 10,000 times that in planktonic form. Clove leaves (Syzygium aromatium) can treat infectious diseases, including candidiasis. This study aimed to analyze whether the ethanol extract of clove leaves (S. aromaticum) destroys the biofilm of C. albicans ATCC 14053. The research designwas pure experimental with a post test control group only design approach. The extraction method used was maceration. Test antibiofilm activity of ethanol extract of clove leaves using microtiter plate biofilm assay method. Measurement of results with a microplate reader was carried out using a wavelength of 595nm in accordance by the wavelength of crystal violet used as a colouring agent. The results showed that ethanol extract of clove leaves (S. aromaticum) has significant effectiveness against the maturation of C. albicans biofilm (p<0.05) with the highest percentage of activity at 20% concentration. The MBEC50 was determined by probit analysis, so the concentration of clove leaf ethanol extract (S. aromaticum) that can eradicate 50% of C. albicans biofilm is located at a concentration of 0.45%. The clinical benefits that can be developed from the results of this study are the potential use of clove leaf ethanol extract as an alternative therapy for C. albicans infection in the form of soap or ointment.